2019
DOI: 10.22373/ekw.v5i2.4356
|View full text |Cite
|
Sign up to set email alerts
|

Isolasi dan Seleksi Bakteri Proteolitik Asal Limbah Cair Tahu Sebagai Dasar Penentuan Agen Pembuatan Biofertilizer

Abstract: Liquid tofu waste has the effect of damaging the environment if treated poorly. The waste contains a reasonably high protein so that it can be used as a substrate for isolation of proteolytic bacteria. Proteases produced by proteolytic bacteria can hydrolyze proteins in liquid tofu waste. The results of protein hydrolysis are amino acids in the form of nitrogen. The nitrogen can be used by plants for nutritional growth so that bioconversion products from proteolytic bacteria can be used as biofertilizers. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…The clear area is an indicator that isolates can utilize protein in the media as a nutritional source. The protease index produced by Candida tropicalis is smaller compared to the protease index produced by isolates from tofu wastewater (Asril & Leksikowati, 2019).…”
Section: Discussionmentioning
confidence: 77%
“…The clear area is an indicator that isolates can utilize protein in the media as a nutritional source. The protease index produced by Candida tropicalis is smaller compared to the protease index produced by isolates from tofu wastewater (Asril & Leksikowati, 2019).…”
Section: Discussionmentioning
confidence: 77%
“…Isolat bakteri yang memiliki indeks pelarut fosfat tertinggi dilakukan uji patogenitas sederhana pada umbi kentang yang telah dimodifikasi (12) . Metode uji patogenitas ini merupakan modifikasi dari Lelliot dan Stead (13) .…”
Section: Pengujian Patogenitas Isolat Bakteri Potensialunclassified
“…Umbi kentang menjadi salah satu sampel model untuk pengujian degradasi pektin yang biasanya ditemukan pada dinding sel tanaman. Indikasi bakteri digolongkan sebagai patogen tanaman yaitu terjadinya lesi pada kentang yang diujikan (12) . Penggunaan kentang sebagai inang model dikarenakan kentang merupakan inang alternatif yang mampu memberikan informasi terhadap patogenitas suatu bakteri uji (32) .…”
Section: Patogenitas Isolat Potensialunclassified
“…Research aimed at exploring proteolytic bacteria has been carried out by calculating the Proteolytic Index (IP), including derived from peat soils (Mahdiyah, 2015), mangrove forest land (Hastuti Sri et al, 2017), Tofu liquid waste (Asril &;Leksikowati, 2019), and on a 72-hour postfermentation red oncom (Lestari et al, 2018). From several studies, potential proteolytic bacteria with varying IP values were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…From several studies, potential proteolytic bacteria with varying IP values were obtained. Five isolates derived from peat soils have proteolytic capabilities with IP 3 (Mahdiyah, 2015), from mangrove forest soil 1.62-2.94 and one of them was identified from the species Vibrio parahaemolyticus (Hastuti Sri et al, 2017), from tofu liquid waste 3.20 (Asril &;Leksikowati, 2019). The formation of a clear zone with a diameter of 78 mm around the bacterial colony showed that protease activity of bacterial isolates from red oncom samples after 72 hours of fermentation (Lestari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%